Feasibility Analysis of Cicalengka Tofu Factory Expansion - Alam, Adelia Shanty; Hasun, Farda; Suryana, Nanang (JTI: Jurnal Teknik Industri, 2024)
Tofu is a popular and affordable protein source widely consumed across Indonesia. The Cicalengka Tofu Factory in Bandung Regency is experiencing increasing demand, resulting in frequent overtime to meet production requirements. The factory plans to expand its production area by utilizing adjacent vacant land to address this challenge. This study evaluates the feasibility of the expansion, forecasting tofu demand until 2026 using time-series analysis with a single moving average method. The proposed expansion aims to increase production capacity from 264 to 396 tofu planks per day, requiring an investment of IDR 1,551,129,586. Financial analysis reveals that without expansion, the Net Present Value (NPV) over the next three years would be IDR 825,211,554, with an Internal Rate of Return (IRR) of 121%. With the expansion, the NPV increases to IDR 972,087,040, with an IRR of 43%. Incremental IRR analysis further supports the expansion, yielding an IRR of 22%, which exceeds the Minimum Attractive Rate of Return (MARR) of 16.36%. These findings validate the expansion plan as a financially viable strategy to enhance production capacity, minimize overtime, and ensure the factory’s long-term sustainability.Keywords: Feasibility Analysis, Expansion, Cicalengka Tofu Factory, Incremental Analysis